Students’ voice on the use of the website with url https://anglofon.com/test-your-legal-english-terminology - Supardi (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Although many scholars have discussed student voice as the topic for their studies, in empirical practice none of them has reported his/her studies on this topic in term of using the website with the URL https://anglofon.com/test-your-legal-english-terminology. To meet this practical gap, the currest researcher reports his experience of teaching Legal English (LE) using this website to 73 law students at the University of Jember (UNEJ) at the third meeting in March 2021. This website was chosen because of its suitability in catering UNEJ law students’ of LE vocabulary mastery. In this context the current study focuses its discussion on the exploration of how useful the website with the URL https://anglofon.com/test-your-legal-english-terminology is in the classroom. For the exploration, 30 minutes before the class ended, the students were asked to write a paragraph regarding their comments on the usefulness or unusefulness of the website. Based on the document of their comments, the data were collected and analyzed using thematic analysis. Finding indicated that with different reasons 56 students (77%) stated that the website was very useful and 17 students (23%) thought that it was useful. From these findings, it indicates that the website with the URL https://anglofon.com/test-your-legal-english-terminology has a positive impact on UNEJ law students in enhancing their LE vocabulary mastery althoguh this website is not the best one. Hopefully, this website can also be used by other teachers in teaching LE.